Coastal ocean and shelf-sea biogeochemical cycling of trace elements and isotopes: lessons learned from GEOTRACES - Charette, M; Lam, P; Lohan, M; Kwon, E; Hatje, V; Jeandel, C; Shiller, A; Cutter, G; Thomas, A; Boyd, P; Homoky, W; Milne, A; et al. (Royal Society, 2016)
Continental shelves and shelf seas play a central role in the global carbon cycle. However, their importance with respect to trace element and isotope (TEI) inputs to ocean basins is less well understood. Here, we present major findings on shelf TEI biogeochemistry from the GEOTRACES program as well as a proof-of-concept for a new method to estimate shelf TEI fluxes. The case studies focus on advances in our understanding of TEI cycling in the Arctic, transformations within a major river estuary (Amazon), shelf sediment micronutrient fluxes, and basin-scale estimates of submarine groundwater discharge. The proposed shelfflux tracer is 228-radium (T1/2=5.75 y), which is continuously supplied to the shelf from coastal aquifers, sediment porewater exchange, and rivers. Model-derived shelf 228Ra fluxes are combined with TEI/228Ra ratios to quantify ocean TEI fluxes from the western North Atlantic margin. The results from this new approach agree well with previous estimates for shelf Co, Fe, Mn, and Zn inputs and exceed published estimates of atmospheric deposition by factors of ~3-23. Lastly,recommendations are made for additional GEOTRACES process studies and coastal margin-focused section cruises that will help refine the model and provide better insight on the mechanisms driving shelf-derived TEI fluxes to the ocean.